Chances and Challenges of Digital Management Proceedings of the International Scientific-Practical Conference (ISPC 2022) - Geibel, Richard C.; Machavariani, Shalva (Springer Proceedings in Business and Economics, 2023)
XII, 250 p. 67 illus., 54 illus. in color.